Electropolymerization, spectroelectrochemistry and electrochromic properties of cross-conjugated and conjugated selenophenothiophenes with thiophene bridge - Turkoglu, Gulsen; Ozturk, Turan (Elsevier BV, 2021)
Abstract Two novel selenophenothiophene homopolymers, P(SeT1) and P(SeT2), were electrochemically prepared for the first time from their corresponding monomers (i) conjugated 2,5-di(thiophen-2-yl)selenopheno[3,2-b]thiophene (1) and (ii) cross-conjugated 2,5-di(thiophen-2-yl)selenopheno[2,3-b]thiophene (2) to explore their electrochromic behaviors. The effects of conjugation and cross conjugation on the electrochromic performances and electrochemistry and spectroelectrochemistry of the polymers were systematically studied. While the cross conjugated polymer film of P(SeT2) displayed a color change from yellow to a light green upon oxidation, the conjugated polymer film of P(SeT1) showed an orange color in the neutral and a claret red in the oxidized state. The polymer P(SeT1), owing to its extended π-conjugation, had a lower optical band gap of 1.82 eV, compared to the polymer P(SeT2) (2.27 eV). Their electrochromic performances displayed that P(SeT2) had a higher optical contrast (46.2%) and a lower response time (oxidation time of 1.34 s at 680 nm). The first electrochemically-synthesized poly(selenophenothiophene) films showed good electrochemical activity and electrochromic properties. Moreover, this pioneering study suggests a new strategy for designing and preparing organic electrochromic materials possessing selenophenothiophene units.